A review of trends, constraints and opportunities of smallholder irrigation in East Africa - Nakawuka, Prossie; Langan, Simon J.; Schmitter, Petra S.; Barron, Jennie (Elsevier, 2018)
Smallholder irrigation expansion would signi cantly increase agricultural production, and reduce food insecurity and poverty levels in East Africa. This paper reviews literature on trends, constraints and opportunities of smallholder irrigation in four East African countries: Ethiopia, Kenya, Tanzania and Uganda. Irrigation development has been slow in these countries, and has been mainly through traditional schemes. Recently, individual irrigation technologies such as small motorized pumps, drip kits, treadle pumps, rope and washer pumpsarebeing promoted.Adoption ofthesetechnologiesandexpansion ofsmallholder irrigationhoweverface a number of challenges including land tenure issues; lack of access to appropriate irrigation technologies, improved agricultural inputs, reliable markets, nance and credit services, and research support; poor transport and communication infrastructures; poor irrigation water management; poor extension systems; and the over dependence on national governments, NGOs and donors for support. Despite these challenges, opportunities exist for smallholder irrigation expansion in East Africa. Such opportunities include: high untapped irrigation potential; rainwater harvesting to improve water availability; high commitment of national governments, NGOs and donors to smallholder irrigation expansion; low cost irrigation technologies adaptable to local conditions; traditional schemes rehabilitation;growing urbanization; and increaseduse ofmobilephones thatcanbeused to disseminate information.